2010
DOI: 10.1638/2009-0254.1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Changes of Plasma Sex Steroids in Captive Breeding Loggerhead Turtles (Caretta caretta)

Abstract: Loggerhead turtles (Caretta caretta) have been laying eggs in an indoor artificial beach since 1995, at the Port of Nagoya Public Aquarium (PNPA). Four individuals landed and laid eggs several times during the breeding period in 1996. Blood samples from these individuals were collected monthly throughout that year in order to investigate the changes in sex steroid hormones (testosterone, estradiol, and progesterone). In addition, detailed investigations were conducted daily during the breeding period on one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
6
10
0
1
Order By: Relevance
“…The iguanid Dipsosaurus dorsalis shows no seasonal change in plasma albumin levels associated with vitellogenesis, and while experimentally injected oestrogen decreased albumin as a proportion of total plasma protein, it had no effect on final plasma albumin concentration (Gerstle & Callard, ). In contrast to these examples, data from sea turtles suggest the opposite phenomenon: nesting Caretta caretta have higher plasma albumin levels than non‐nesting individuals (Deem et al., ), and plasma albumin concentration declines over the nesting period in Eretmochelys imbricata and Dermochelys coriacea (Honarvar et al., ; Goldberg et al., ) at the same time that plasma oestrogen concentration is declining (Wibbels et al., ; Rostal et al., ; Dobbs et al., ; Rostal, ; Kakizoe et al., ). These nesting sea turtles are actually post‐vitellogenic, but in contrast to the reptiles mentioned above, they have elevated oestrogen levels at the same time that they have elevated albumin levels.…”
Section: Lipid Metabolism During Vitellogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The iguanid Dipsosaurus dorsalis shows no seasonal change in plasma albumin levels associated with vitellogenesis, and while experimentally injected oestrogen decreased albumin as a proportion of total plasma protein, it had no effect on final plasma albumin concentration (Gerstle & Callard, ). In contrast to these examples, data from sea turtles suggest the opposite phenomenon: nesting Caretta caretta have higher plasma albumin levels than non‐nesting individuals (Deem et al., ), and plasma albumin concentration declines over the nesting period in Eretmochelys imbricata and Dermochelys coriacea (Honarvar et al., ; Goldberg et al., ) at the same time that plasma oestrogen concentration is declining (Wibbels et al., ; Rostal et al., ; Dobbs et al., ; Rostal, ; Kakizoe et al., ). These nesting sea turtles are actually post‐vitellogenic, but in contrast to the reptiles mentioned above, they have elevated oestrogen levels at the same time that they have elevated albumin levels.…”
Section: Lipid Metabolism During Vitellogenesismentioning
confidence: 99%
“…Levels of vitellogenin and triglycerides may rise as a side‐effect of elevated oestrogen levels (Smelker et al., ). Oestrogen is involved not only in coordinating vitellogenesis, but also other events of reproduction including nesting (Owens, ; Kakizoe et al., ). Thus the liver may be ‘incidentally’ stimulated to produce vitellogenin and triglycerides at times when they are not necessary for vitellogenesis per se .…”
Section: Lipid Metabolism During Vitellogenesismentioning
confidence: 99%
“…This has also been shown in juvenile loggerhead turtles in USA waters, where T concentrations were reliable indicators of sex only during the summer months, when water temperatures were >23°C (Braun-McNeill et al 2007), but the opposite was true for adult loggerhead turtles (Wibbels et al 1987, Owens 1997. Seasonal variation in T has also been shown for other reptiles (Gowan et al 2010, Kakizoe et al 2010, Hamlin et al 2011, Boretto et al 2012, and may maxi mise mating opportunities during the season when females are receptive. For juveniles this may serve no purpose until sexual maturity, but the drivers of the seasonal variation are currently not understood.…”
Section: Methodsmentioning
confidence: 75%
“…It was thought that it was caused by the effective accumulation of Ca which was to be used in the next nesting period. In the annual observation of Ca and the ratio of Ca/P, it was found that they increased from previous autumn as estradiol [9], TP, and lipids did. Therefore, it shows that females prepare Ca along with TP and lipids for half a year for the next egg laying.…”
Section: Discussionmentioning
confidence: 93%
“…Both Ca and P indicated higher values in the egg laying time than those between egg layings. Moreover, considering ovulation is expected to occur within several days after egg laying based on progesterone concentration change; the preparation for the next egg formation has already started at the time of egg laying in sea turtles like the poultries [9]. Although the ratio of Ca/P indicated the extremely high value on the seventh day after each egg laying, it is considered that eggs go into shell gland and their egg formation is undertaken actively at this time.…”
Section: Discussionmentioning
confidence: 99%